2017
DOI: 10.3390/e19090452
|View full text |Cite
|
Sign up to set email alerts
|

An Approach for Determining the Number of Clusters in a Model-Based Cluster Analysis

Abstract: Abstract:To determine the number of clusters in the clustering analysis that has a broad range of applied sciences, such as physics, chemistry, biology, engineering, economics etc., many methods have been proposed in the literature. The aim of this paper is to determine the number of clusters of a dataset in a model-based clustering by using an Analytic Hierarchy Process (AHP). In this study, the AHP model has been created by using the information criteria Akaike's Information Criterion (AIC), Approximate Weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(120 citation statements)
references
References 57 publications
0
105
0
1
Order By: Relevance
“… Note : An analytic hierarchy process based upon all fit indices presented above from Akogul and Erisoglu (2017) suggested that the 3 class solution was optimal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Note : An analytic hierarchy process based upon all fit indices presented above from Akogul and Erisoglu (2017) suggested that the 3 class solution was optimal.…”
Section: Resultsmentioning
confidence: 99%
“…The purpose of this study was to evaluate: (a) Whether students that responded positively to a Tier 2 reading fluency intervention belong to distinct profiles based upon their screening score at the beginning of the year and T A B L E 1 Model fit indices for 1-5 class solutions for student response patterns Note: An analytic hierarchy process based upon all fit indices presented above from Akogul and Erisoglu (2017) suggested that the 3 class solution was optimal. Abbreviations: Adjusted BIC, BIC adjusted for sample size; AIC, Akaike information criterion; BIC, Bayesian information criterion; BLRT, Bootstrap likelihood ratio test (p value); % Min, percentage of sample in smallest class; % Max, percentage of sample in largest class.…”
Section: Discussionmentioning
confidence: 99%
“…Information criteria and likelihood ratio tests were used to identify the optimum number of latent classes. We followed an analytic hierarchy process based on the fit indices BI, AIC, AW, CLC, and KIC (60). We also considered the results of the Bootstrap Likelihood Ratio Test [BLRT; (61)].…”
Section: Discussionmentioning
confidence: 99%
“…The entire dataset is modeled by a mixture of these distributions. One study has applied this method where AHP (Analytical Hierarchy Process) is used to determine the effective number of clusters [13]. SOM (Self-Organizing Maps) is one of Artificial Neural Network architecture which is used for clustering that works with one type of machine learning that is unsupervised learning.…”
Section: Introductionmentioning
confidence: 99%